Effect of Indole Butyric Acid (IBA) and Coconut Water on The Growth of Orchid Plant Shoots (Cattleya sp.) in Vitro - Ade Alya Yasmint; Fauziyah Harahap (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
This study aims to observe the effect of Indole Butyric Acid (IBA) concentration and coconut water on the growth of orchid plant shoots of Cattleya sp. In vitro using the tissue culture method. The research was conducted at the YAHDI Tissue Culture Laboratory from March to July 2024. There were 9 treatments with a combination of IBA concentrations (0, 1, 2 mg/l) and coconut water (0, 50, 100 ml/l), which were repeated 3 times each, resulting in a total of 27 experimental units. The variables observed included the time of emergence of shoots, the number of shoots, the number of leaves, and the height of the plantlet. The results showed that a coconut water concentration of 100 ml/l provided the best bud growth, while an IBA concentration of 1 mg/l and coconut water of 100 ml/l produced the highest number of leaves. However, variance analysis showed that the application of IBA and coconut water did not have a significant effect on the number of shoots, the number of leaves, and the height of orchid plantlets at the age of 6 MST. Observations showed that the interaction between IBA and coconut water was not optimal enough to stimulate bud growth, and the use of younger orchid leaves gave the best results. This study provides insight into the use of coconut water in tissue culture to improve the growth of Cattleya orchids, although its effectiveness is still limited to certain concentrations.